Developing Business Translation Material for English Education Department Students at University of Muhammadiyah Gresik - Erisafitri, Fajriyani (Jetlal, 2017)
Translation is a language competence which combines reading and writing skills. It is worth the learning, especially for English department students. Through learning translation, the students are able to not only enhance their translation skill, but also prepare for the challenges of finding jobs after they graduate. One of the useful translation topics to be learned is business. Based on those reasons, this study was intended to create a business translation material for English education department students at University of Muhammadiyah Gresik. This study employed Research and Development design and Asmara’s ADDIE (Analyze, Design, Develop, Implement, Evaluate) model. 21 senior students of English language education department at University of Muhammadiyah Gresik who have passed translation course were involved in the study. The need analysis data were gathered through questionnaire. The result of the questionnaire was considered in creating the material, which is developed following Harmer’s ESA (Engage, Study, Activate) approach. The need analysis results reveal that the students need the material which focuses on enhancing translation skills and enriching vocabulary as well as provides basic information about business letters as the topic of the material. From the result of expert validation and questionnaire after try-out, some adjustments are made to the material. The adjustments are presenting more explanation of business letters material, adding more vocabularies, giving some pictures, and providing conclusion at the end of each chapter. To conclude, the students need the material which focuses on not only skills enhancement, but also vocabulary enrichment. This study involved students who have passed translation course, expected to use their experience in translation learning to be considered in creating the material. Based on the results, the recommendations are given to English language education department students, translation lecturers, and future researchers to use both the data of the results and the product of this study effectively.